Задача термоупругости для полусферического тела с покрытием - Бондаренко, Н.А.; Жуковский, А.Н.; Мечник, В.А.; Панов, А.В.; Казьмин, А.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The axisymmetric problem of thermoelasticity for spherical diamond bit in hole drilling
conditions is solved. The peculiarity of the problem is in that stresses themselves depend on temperature nonlinearily but the equilibrium conditions include the components of volume force vector. The problem solution is represented in terms of Legendre polinomials and spherical functions which enable to define the components of quasi-static thermoelastic stresses at a random point of time and to analyze the main factors influencing on kinetics of the given process.